Comparative Analysis of the Presence of University Professors from Southern Ecuador in Scientific Social Networks. - Benítez Arrobo, Karen Michelle; Hinojosa-Becerra, Mónica; Maldonado-Espinosa, Mónica; Marín-Gutiérrez, Isidro (Springer Nature, 2021)
Scientific social networks such as ResearchGate, Academia.edu, and the Google Scholar platform, have become a tool to make the work of researcher professors visible, measure the impact of their publications, and interact with other researchers. Hence the need to analyze the presence in scientific social networks of the Faculties of Social Sciences and Socio-Humanistic Area of the universities belonging to Zone 7 of southern Ecuador, Universidad Técnica Particular de Loja (UTPL), Universidad Técnica de Machala (UTMACH) and Universidad Nacional de Loja (UNL). The interaction with professors, the RS Score index in Research Gate, the h index in Google Scholar, and the presence in Academia.edu were observed. In the case of the Faculties analyzed, the professors do not take advantage of the benefits of scientific networks, which affects the visibility of scientific production and the dissemination of the research results.
Informada la autora de las políticas editoriales de Springer, nos envía el documento adjunto como versión aceptada.
Keywords: Universidades; Investigación; Academic scientific networks; Science dissemination; University research